Turkey as a mediator : stories of success and failure - Eralp, Doğa Ulaş, 1978- (Lexington Books, 2016)
This book offers a systematic overview of successes and failures of Turkey's mediation initiatives in fragile and conflict-affected societies in the Middle East, western Balkans, and sub-Saharan Africa. It analyzes the narratives that guide Turkish mediation, the tools used by the Turkish government, and Turkey's evolving self-image as a mediator.